Merging optimization and control in power systems : physical and cyber restrictions in distributed frequency control and beyond - Liu, Feng (Electrical engineering teacher) (Hoboken, New Jersey : John Wiley & Sons, 2022)
"With the increasing penetration of renewable energy sources and the promotion of Energy Internet, the power system is in a significant transition period, bringing major challenges for power system control. This book aims to provide a comprehensive and systematic framework to design distributed optimal controllers with cyber and physical restrictions. It introduces the idea of bridging the gap between optimization and control and shows how to handle various kinds of physical and cyber restrictions or special considerations. Related state-of-the-art methods are introduced and illustrated in detail with hands-on examples for readers to learn how to use them to address real control design problems in practice. Requiring foundational knowledge of power system analysis, operation, and dynamics, convex optimization theory, and control theory, this is an advanced level treatment for students, academics, and professional engineers"--
Includes index.
Keywords: Electric power systems -- Control